Analysis of Prophylactic Antibiotic Administration in Obstetrics, Gynecology, Orthopedics, and Gastrointestinal Surgery at Pondok Indah Bintaro Jaya Hospital January-March 2024 - Nurjaman, Evelina Endang; Andriani, Helen (Eduvest - Journal of Universal Studies, 2025)
The use of presurgical antibiotics is common, but adherence to guideline is low. Improper use can lead to antibiotic resistance. A preliminary study was conducted at RSPI Bintaro Jaya hospital between October and December 2023. The study found that the correct type of antibiotic and the timing of administration (30-60 minutes before incision) were both below 60% adherence. Research objectives is to analyze the appropriateness and rationality of pre-surgical antibiotics prescriptions and to evaluaste the causes of noncompliance. The research used a mixed-methods approach. Descriptive statistics to analyze prescribing patterns. Semi-structured interviews to understand the reasons behind prescribing practices. Research finding: Adherence to prescribing guidelines for antibiotic prophylaxis was less than 60%. While doctors had the capability and opportunity to prescribe correctly, concerns about infection risk and surgical outcomes influenced their motivation, leading to potentially less judicious use of antibiotics.